Prevalence of Periodontitis among Thermal Power Station Workers in South India - Palaneeswaran Kamalashankar; Sivalingam Balaji; Annamalai Indra; Shobana G; Aziz Mac B. Abdul; Nagappan Nagappan (Wolters Kluwer Medknow Publications, 2024)
The occupational stressors has an effect on overall health and dental health. Oral health is a vital aspect of general health. The current study was performed to assess the periodontitis among thermal power station workers in South India. Pilot study was done for 52 mine workers and based on the periodontal disease prevalence among them, the sample size was calculated as 603 subjects. The data collection was done using WHO 1997 proforma. Among the total study population, about 92 (30%) thermal power station 1 workers and 83 (28.1%) thermal power station 2 workers had pocket 4-5 mm, one (0.2%) thermal power station, 2 worker had pocket 6 mm or more thermal power station I workers, and 23 (7.8%) thermal power station 2 workers had 6 - 8 mm attachment loss. Only 1 (0.3%) thermal power station I worker had 9 - 11 mm attachment loss. In the current study, nearly 70% mine workers had calculus, nearly 30% had pocket 4-5 mm, and only 0.2% Mine II workers had pocket measuring 6 mm or more.